2011
DOI: 10.4103/0253-7176.92062
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Antidepressant Drugs Research Articles Published in Indian Medical Journals

Abstract: Aim and Objective:Quality of methodological and statistical parameters published in various Indian Medical Journals are usually debated in terms of appropriateness. Aim of this manuscript is to analyze and validate efficacy studies on antidepressant drugs published in Indian Medical Journals regarding quality of various methodological and statistical parameters used.Materials and Methods:An in-depth review of Efficacy studies on Antidepressant published in Indian Medical Journals was conducted. Articles were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This result is similar to a study reported in the Indian journal of Psychiatry where only 1 study mentioned sample size calculation. 9 Considering this small fraction, we consider this area as a scope for immense improvement.…”
Section: Discussionmentioning
confidence: 99%
“…This result is similar to a study reported in the Indian journal of Psychiatry where only 1 study mentioned sample size calculation. 9 Considering this small fraction, we consider this area as a scope for immense improvement.…”
Section: Discussionmentioning
confidence: 99%